The roles of employers and trade unions in immigration and welfare state policymaking. (November 2020) - Knotz, Carlo; Fossati, Flavia; Scalise, Gemma; Hooijer, Gerda
Whether and under which conditions immigrants should be admitted and obtain access to employment and social security is an issue of continuously high political salience across the advanced democracies. Unions and employers, as traditionally influential actors in immigration and social policymaking, have important roles to play in this area, but their exact preferences, strategies and behaviour are theoretically difficult to determine and are still only partly understood. This article outlines a series of research problems regarding the roles of social partners in the social and economic integration of immigrants and discusses how the articles contained in this special issue address these problems.